Addressing an Overlooked Population: The Role of Discrimination and Violence in Depression Among South Asian Female College Students - Ranjani, Anirudhan; Nitasha, Nagaraj; Amita, Vyas (Journal of Public Health International, 2025)
South Asian female college students in the United States face mental health challenges shaped by intersecting experiences of discrimination and violence. This study examined how discrimination and violence contribute to depression in this population. An anonymous, cross-sectional, web-based survey (N=673) was distributed nationally through South Asian organizations, listservs, and social media. Validated measures assessed day-to-day discrimination, college-based discrimination, experiences of violence during college, and depression (PHQ-9). Bivariate analyses and multivariate linear regression examined associations, adjusting for sociodemographic factors. Over half of participants (51.1%) reported college-based discrimination, 66.1% reported experiencing violence during college, and 25.7% met the criteria for depression. In adjusted models, day-to-day discrimination (β=0.261, p<0.001) and college violence (β=0.207, p<0.001) were significant predictors of depression. Bisexual and questioning/unsure students also reported higher depression scores than heterosexual peers. Discrimination and violence are key social determinants of mental health among this population. Findings underscore the need for culturally responsive mental health services, intersectional campus policies, and evidence-based interventions to promote health equity among minority women in higher education.
Keywords: South Asian; College Health; Discrimination; Gender-based Violence; Depression; Mental Health